HUBUNGAN TINGKAT PENGETAHUAN NUTRISI DENGAN KADAR GULA DARAH NUCHTER POST PRANDIAL PADA PASIEN DIABETES MELLITUS TIPE 2 DI POLIKLINIK RUMAH SAKIT ISLAM SUKAPURA JAKARTA TAHUN 2019 - Rizki Padliah; Kusdiah Eny S (Afiat, 2019)
Introduction Diabetes Mellitus patients need knowledge in carrying out dietary therapy, especially the fulfillment of nutrition so that type 2 DM patients can control GD NPP levels so that no other disease complications occur in type 2 DM patients. The purpose of this study is to determine the relationship of nutritional knowledge level of DM type 2 patients with GD levels NPP. The research method is descriptive descriptive, with cross sectional approach. Sampling by purposive sampling as many as 81 respondents using DM nutrition knowledge questionnaire instrument. The analysis used univariate by using a percentage system in the statistical system and bivariate using chi-square with α = 5%. The results showed that of 81 respondents with good knowledge, 24 respondents (30%), not well knowledgeed, 57 respondents (70%). From the fisher's exact test analysis, the p value is 0,000, which means that the p value is less than α = 5%, then the null hypothesis (Ho) is rejected. Conclusion there is a relationship between the level of knowledge of nutritional fulfillment with GD NPP levels in type 2 DM patients. Suggestions that the Islamic Hospital in Sukapura Jakarta can increase health promotion and education for polyclinic visitors so that DM patients can carry out the DM diet according to the schedule, type of food and amount calorie requirements.